Response of two Acacia species to drought and inoculation with an ectomycorrhizal fungus - Osonubi, O.; Mulongoy, K. (Springer, 1991)
Inclusion of trees in cropping systems is an efficient way to recycle nutrients and replenish soil organic matter. In the tropics, P deficiency is commonplace, and rains are erratic in many areas. Mycorrhizal fungi are known to enhance P uptake of the host-plant in low-P soils, and to improve its water relations under drought conditions.